2020
DOI: 10.3390/medicina56090444
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Equine-Assisted Therapies or Horse-Riding Simulators on Chronic Pain: A Systematic Review and Meta-Analysis

Abstract: Background and objectives: Chronic pain is a complex global public health problem that affects the health status, quality of life, activities of daily living, and different work-related variables. Riding a horse may lead to some benefits in chronic pain patients through the improvement of postural control and other biopsychosocial processes. Therefore, this systematic review and meta-analysis aimed to evaluate the effects of horse riding (with real or simulated horses) on chronic pain. Materials and methods: A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 45 publications
0
32
0
Order By: Relevance
“…In addition, this is consistent with the results found in two reviews. Collado-Mateo et al [52] concluded that horse-riding simulators are a promising tool to reduce pain intensity in low back patients, but the interpretation of the results must be performed with extreme caution due to the large heterogeneity, the low number of studies, and the potential risk of bias. Ren et al [53] also found significant differences in favor of horse simulator riding compared with control in pain intensity postintervention and severity of disability in people with CLBP.…”
Section: Discussion With Other Reviewsmentioning
confidence: 99%
“…In addition, this is consistent with the results found in two reviews. Collado-Mateo et al [52] concluded that horse-riding simulators are a promising tool to reduce pain intensity in low back patients, but the interpretation of the results must be performed with extreme caution due to the large heterogeneity, the low number of studies, and the potential risk of bias. Ren et al [53] also found significant differences in favor of horse simulator riding compared with control in pain intensity postintervention and severity of disability in people with CLBP.…”
Section: Discussion With Other Reviewsmentioning
confidence: 99%
“…This was suggested in a previous similar meta-analysis study which showed promising outcomes of both equine-assisted therapies and horse-riding simulators; however, they requested more studies to compare the effects of equine-assisted therapies and horse-riding simulators. 42 Well-conducted randomised controlled trials are needed to assess these factors and the combination of different ages, ethnicity and other variants of subjects;…”
Section: Discussionmentioning
confidence: 99%
“…Also, psychological, physiological and psychosocial results with equine‐assisted therapies and horse‐riding simulators are needed to be clarified. This was suggested in a previous similar meta‐analysis study which showed promising outcomes of both equine‐assisted therapies and horse‐riding simulators; however, they requested more studies to compare the effects of equine‐assisted therapies and horse‐riding simulators 42 . Well‐conducted randomised controlled trials are needed to assess these factors and the combination of different ages, ethnicity and other variants of subjects; since our meta‐analysis study could not answer whether different ages, ethnicity and gender are associated with the results.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis of seven studies showed that exercise training reduced fear-avoidance behaviours; 11 another meta-analysis of five studies showed that horse riding simulator exercise training reduced pain intensity, yet concluded evidence was lacking for real horse riding (equine-assisted therapy). 12 Additionally, evidence from a recent randomised clinical trial showed that while beneficial for reducing pain intensity, disability and fear avoidance, 13 Evidence for integrating exercise training into the multidisciplinary management of non-specific chronic low back pain strength and conditioning exercise training program did not improve the health of degenerated intervertebral discs in a cohort of patients with non-specific CLBP. 14…”
Section: Evidence Basementioning
confidence: 99%